The Change of Support Problem (COSP) and its Implications for Urban Analysis: Some Evidence from a Study of the European Urban System - Boris A. Portnov (European Regional Science Association (ERSA), 2010)
The Change of Support Problem (COSP) reflects a possibility that the outcome of an urban analysis may depend critically on the researcher's choice of territorial units. To verify this assumption, the present study examines the association between population growth and population size of localities, using population growth data for two levels of geographic resolution - 4,667 local administrative units (i.e., municipalities) and 2189 contiguous urban areas in 40 European countries. According to our findings, when individual localities are considered, the growth of localities appears to be strictly proportional to population size, but 'dissipates' when the settlement system is disaggregated into two urban sub-systems, formed by well-positioned localities and poorly positioned ones. Concurrently, for urban areas, a strong positive association between population size and growth emerges both before and after controlling for location attributes. However, this association between population size and growth is not especially strong, if favorably and unfavorably located urban areas are looked at in separation.
Keywords: 330; Urban growth; European urban system; urban areas; location attributes; Gibrat's Law